Effects of selective logging on dynamics and composition of woody seedlings in a tropical secondary forest - Redondo-Brenes, Álvaro (Editorial Tecnológica de Costa Rica, 2012)
This study was conducted in a logging road in a 28 years old secondary forest in theAtlantic lowlands of Costa Rica. We gathered information from three different microhabitats:track road, edge road and an adjacent logged forest. The main objective was to study thedynamics and composition of woody seedlings ³ 20 cm height and < 1 cm dbh. Sets of 5m2 quadrats were laid out at 15 meters intervals in the logging road (320 m long). Datawere collected at 12, 19 and 25 months after logging. The author registered density,species richness and diversity, height growth rate, recruitment and mortality. Seedlingsgrowing in the road quadrats had the highest density, growth rate and recruitment. Seedlingdensity in the logging track and edge road did not differ significantly. Mortality rate did notdiffer significantly among the three microhabitats. Species diversity, based on Shannon’sand Simpson’s index, was highest in the logged forest quadrats, but the road quadrats hadthe highest species density. The most abundant species in the track road were Vochysiaferruginea (Mart), Hampea appendiculata (Donn Sm) Standl, and Ossaea brenesii (Standl).V.ferruginea accounted for more than half of the density per plot. The microhabit conditionscreated by logging activities, especially in the track and edge road may have favored theestablishment of pioneer and other light -demanding species in these open areas regardingthe adjacent logged forest. Long-term studies should be conducted in logged secondaryforests of different ages to understand processes of forest recovery after anthropogenicdisturbance. Furthermore, the role of soil conditions and light availability in these processesneeds to be investigated in more detail.